(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this Research Paper of the Organic light Emitting diode performance on electro-luminescence postulates, Organic light Emitting diode is industrially convenient due to its low power consumption; it may be utilized as a display. The paper objective is design a high efficiency OLEDs, addressing both electrical and optical facet. The tool, Silvaco TCAD is being used to measure the luminescence intensity of bi-layer and triple-layer OLED technologies. The electrical and optical aspects of 2-layer and 3-layer OLEDs, similarly luminescence power versus anode voltage and current value, while also exciton state, have been modeled. The operational distribution about Langevin recombination inside complexes, as well as the physical design, technologies, and concepts of OLED, have been investigated.